Lipid biomarkers and long-term risk of cancer in the Women's Health Study. Issue 6 (20th April 2016) - Chandler, Paulette D; Song, Yiqing; Lin, Jennifer; Zhang, Shumin; Sesso, Howard D; Mora, Samia; Giovannucci, Edward L; Rexrode, Kathryn E; Moorthy, M Vinayaga; Li, Chunying; Ridker, Paul M; Lee, I-Min; et al.
ABSTRACT: Background : Lipid biomarkers, such as HDL-cholesterol concentrations, have been shown to have positive, inverse, and null associations with total, breast, and colorectal cancer risks. Studies of novel lipid biomarkers, such as apolipoprotein A-I (apo A-I) and apolipoprotein B-100 (apo B-100), and cancer risk have been sparse, to our knowledge. Objectives: We evaluated the prospective association of total, breast, colorectal, and lung cancers and cancer mortality with circulating lipid biomarkers in 15, 602 female health professionals in the Women's Health Study (aged ≥45 y, free of cardiovascular disease and cancer, and without hormone replacement therapy or lipid-lowering medications at baseline). Design: Cox regression models estimated HRs of cancer endpoints (19 y median follow-up) across quartiles 1 (reference) to 4 of each lipid biomarker after adjustment for cancer risk factors. Results: Confirmed cases included 2163 incident cancer cases (864 breast, 198 colorectal, and 190 lung cancers) and 647 cancer deaths. Total cancer risk was significantly lower in the highest quartile of apo A-I (adjusted HR: 0.79; 95% CI: 0.70, 0.90; P -trend = 0.0008) and HDL cholesterol (HR: 0.85; 95% CI: 0.75, 0.97; P -trend = 0.01). For site-specific cancers, significant associations included colorectal cancer risk with HDL cholesterol (HR: 0.63; 95% CI; 0.41, 0.98; P -trend = 0.03), triglycerides (HR: 1.86; 95% CI: 1.17, 2.97; P -trend = 0.02), and apo B-100 (HR: 1.60; 95% CI: 1.03, 2.49; P -trend = 0.006) and lung cancer risk with HDL cholesterol (HR: 0.59; 95% CI: 0.38, 0.93; P -trend = 0.01). LDL cholesterol was not significantly associated with risk of total cancer or any site-specific cancers. In time-dependent models that were adjusted for the use of a lipid-lowering medication after baseline, these associations remained. Conclusions: Lipids were associated with total, lung, and colorectal cancer risks in women. Lifestyle interventions for heart-disease prevention, which reduce apo B-100 or raise HDL cholesterol, may be associated with reduced cancer risk. The Women's Health Study was registered at clinicaltrials.gov as NCT00000479.